Pengaruh Good Corporate Governance, Financial Distress, dan Return On Equity Pada Voluntary Auditor Switching - Peranian, Ngurah Agung; Mimba, Putu Sri Harta (E-Jurnal Akuntansi, 2018)
The auditor switching issue becomes very crucial for agent and principal due to agency conflict. This study aims to determine the effect of good corporate governance, financial distress, and return on equity on voluntary auditor switching. This study concerns on mining company that listed in Indonesia Stock Exchange and following Corporate Governance Perception Index started from 2008-2015. Sample were obtained by saturation sample method. The number of samples were 6 companies within 32 of observations. The data analysis technique used is logistic regression. The results show that good corporate governance, financial distress, and return on equity does not affect significanty voluntary auditor switching. Keywords : GCG, DER, ROE, Auditor Switching